UPLC-TOF-MS Characterization and Identification of Bioactive Iridoids in Cornus mas Fruit - Shixin Deng; Brett J. West; C. Jarakae Jensen (Journal of Analytical Methods in Chemistry)
Cornus mas L. is indigenous to Europe and parts of Asia. Although Cornus is widely considered to be an iridoid rich genera, only two iridoids have been previously found in this plant. The lack of information on taxonomically and biologically active iridoids prompted us to develop and optimize an analytical method for characterization of additional phytochemicals in C. mas fruit. An ultra performance liquid chromatography (UPLC) coupled with photodiode array spectrophotometry (PDA) and electrospray time-of-flight mass spectrometry (ESI-TOF-MS) was employed and mass parameters were optimized. Identification was made by elucidating the mass spectral data and further confirmed by comparing retention times and UV spectra of target peaks with those of reference compounds. Primary DNA damage and antigenotoxicity tests in E. coli PQ37 were used to screen the iridoids for biological activity. As a result, ten phytochemicals were identified, including iridoids loganic acid, loganin, sweroside, and cornuside. Nine of these were reported for the first time from C. mas fruit. The iridoids did not induce SOS repair of DNA, indicating a lack of genotoxic activity in E. coli PQ37. However, loganin, sweroside, and cornuside did reduce the amount of DNA damage caused by 4-nitroquinoline 1-oxide, suggesting potential antigenotoxic activity.